Highly efficient genome editing in N. gerenzanensis using an inducible CRISPR/Cas9–RecA system - Yue, Xue; Xia, Tianyu; Wang, Shuai; Dong, Huijun; Li, Yongquan (Biotechnology letters, 2020)
Objective To develop an inducible CRISPR/Cas9–Recombinase A (RecA) system to manipulate genes in Nonomuraea gerenzanensis effectively. Results Compared with traditional homologous recombination, the inducible CRISPR/Cas9 system achieved 68.8% editing efficiency, whereas, with both the inducible Cas9 and the overexpressed RecA, the efficiency of the combined genome editing system reached 100%. The dbv23 -deleted mutant obtained by the inducible CRISPR/Cas9–RecA system was confirmed to produce more A40926 with an approximate yield of 200 mg L −1 than that of around 150 mg L −1 produced by the wild-type strain. Conclusions This inducible CRISPR/Cas9–RecA system was successfully constructed and can be utilized as an efficient genome editing tool for Actinomyce s able to shorten editing time simultaneously.